Preeclampsia - Ramos, José Geraldo Lopes; Sass, Nelson; Costa, Sérgio Hofmeister Martins (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2017)
The authors review hypertensive disease during pregnancy with an academic and practical view, and using the best evidence available. This disease, which is the most important clinical disease in Brazilian pregnant women, may have its incidence reduced with prevention through the use of calcium and aspirin in pregnant women at risk. Previously, it was a disease that presented with hypertension with proteinuria, but it has now been classified with new clinical parameters besides proteinuria. Morbidity and mortality should be reduced in a continental country such as Brazil using protocols for the early treatment of complications by calculating severe outcomes in preeclampsia. The early treatment of acute hypertension, use of magnesium sulfate and early hospitalization in cases of preeclampsia are concepts to pursue the reduction of our pregnant women's mortality.
Keywords: pregnancy arterial hypertension; preeclampsia; HELLP syndrome; high risk pregnancy; pregnancy complications